High-velocity impact investigation on thermoplastic polyurethane/CFRP T-stiffened panel. (2021) - Rizzo, F.; D'Agostino, T.; Cuomo, S.; Pinto, F.; Meo, M.
Abstract: In this work, an experimental and numerical study of the High Velocity Impact (HVI) behaviour for hybrid structures was presented. HVI at different velocities were carried out on the structures, evaluating failure phenomena and impact damage using high-speed camera and ultrasound techniques (C-scan). In order to predict the complex impact response and damage extension in the structure, a 3D explicit Finite Element Model (FEM) was developed for each structure using a commercial LS-DYNA software. Experimental and numerical results were then presented showing a good correlation with an error between the 6% and 17% in terms of absorbed energy and damage extension. Afterwards, an optimisation analysis was carried out on the numerical model in order to identify the best design parameters when a TPU layer is introduced in the lamination sequence of the material for damage mitigation purposes. Results were presented reporting a reduction of at least 54% in absorbed energy, damage extension and maximum indentation respectively when 1 mm thick Thermoplastic Polyurethane (TPU) layer is applied on the Carbon Fibre Reinforced Polymer (CFRP) impact surface.